Return to Sport After Arthroscopic Capsular Repair in Elite Baseball Players. Issue 2 (24th February 2023) - Uffmann, William J.; ElAttrache, Neal S.; Youssefzadeh, Keon; Carbone, Andrew; Limpisvasti, Orr
Background: Chronic attritional midsubstance capsular tears arising from repetitive throwing stress are a rare but important source of pain and dysfunction in elite baseball players; however, little is known regarding outcomes after arthroscopic capsular repair. Purpose: To evaluate the patient-reported outcomes and return-to-sport (RTS) rates after arthroscopic capsular repair in elite baseball players. Study Design: Case series; Level of evidence, 4. Methods: We identified 11 elite-level baseball players who were treated with arthroscopic repair for a midsubstance glenohumeral capsular tear by a single surgeon with a uniform approach and a standardized postoperative protocol between 2012 and 2019. All players had at least 2 years of follow-up data. Demographic data and concomitant surgical procedures were recorded. Preoperative and postoperative Kerlan-Jobe Orthopaedic Clinic (KJOC) scores and Single Assessment Numeric Evaluation (SANE) scores were collected in a subset of the cohort, and statistical comparisons were made. A telephone survey was conducted to determine the patients' RTS level and outcome scores. Statistical comparisons between preoperative and postoperative outcomes scores were made using t tests. Results: Eight major league players, 1 minor league player, and 2 collegiate players were included. There were 9 pitchers, 1 catcher, and 1 outfielder. All patients had debridement of the posterosuperior labrum and rotator cuff. Two pitchers underwent a rotator cuff repair, and 1 outfielder underwent a posterior labral repair. The mean age at the time of surgery was 26.9 years (range, 20-34 years), with a mean follow-up of 3.5 years (range, 2.6-5.9 years). There were significant preoperative versus postoperative improvements in the mean KJOC (20.6 vs 89.8; P = .0002) and SANE (28.3 vs 86.7; P = .001) scores. All patients reported a high degree of satisfaction. At a mean of 16.3 months (range, 6.5-25.4 months), 10 of 11 (90.1%) players met the Conway-Jobe good or excellent criteria for RTS. Conclusion: Arthroscopic capsular repair provided significant improvements in functional outcomes in elite baseball players, high levels of patient satisfaction, and high levels of RTS.